The Relationship of Online Learning and Information Technology with Cognitive, Affective, and Psychomotor Abilities - Sidik Awaludin; Usman Chatib Warsa; Soetrisno Soemardjo; Elly Nurachmah; Arum Atmawikarta; Dwi Novitasari (Jurnal Keperawatan Indonesia, 2024)
The COVID-19 pandemic had a significant impact on education in nursing programs. Changes in the learning system were followed by changes in learning methods and information technology as a means of support. In fact, mastery of learning methods and information technology support is still not optimal. To improve students’ cognitive, affective, and psychomotor capacities, lecturers must grasp numerous learning approaches and information technology. This study aimed to examine the relationship of mastery of online learning methods and information technology assistance with nursing students’ cognitive, emotional, and psychomotor capacities in Indonesia. The design of this study was a cross-sectional internet-based survey. The instrument was an online questionnaire using a Google Docs form. The sample size was 582 participants. Simple random sampling was used as the sampling technique. Statistical analysis used Pearson’s correlation test. In terms of education level, the results of the research show that the majority of the participants are from the diploma level (44.2%), followed by undergraduate (26.1%), professional nursing (18.6%), master (8.8%), specialist (1.4%), and doctoral (1.0%). A significant relationship (p < 0.05) was found between mastery of online learning methods and information technology support and cognitive and psychomotor abilities in a positive direction. No relationship was found with affective abilities. Mastery of learning methods and information technology support were correlated with the achievement of cognitive and psychomotor abilities. Specific online learning methods are needed to achieve students’ effective abilities. Keywords: COVID-19, information technology, learning methods, nursing, pandemic   Abstrak Hubungan Pembelajaran Online dan Teknologi Informasi dengan Kemampuan Kognitif, Afektif, dan Psikomotor. Pandemi COVID-19 berdampak buruk pada pendidikan di program studi keperawatan. Perubahan sistem pembelajaran diikuti dengan perubahan metode pembelajaran dan teknologi informasi sebagai sarana penunjang. Kenyataannya, penguasaan metode pembelajaran dan dukungan teknologi informasi masih belum optimal. Dosen dituntut menguasai berbagai metode pembelajaran dan teknologi informasi untuk mencapai kemampuan kognitif, afektif, dan psikomotorik mahasiswa. Tujuan penelitian yaitu mengetahui hubungan antara penguasaan metode pembelajaran online dengan dukungan teknologi informasi terhadap kognitif, afektif, dan psikomotorik kemampuan mahasiswa keperawatan di Indonesia. Desain penelitian ini adalah survei cross sectional berbasis internet, prosedur penelitian ini yaitu dengan mengirimkan kuesioner melalui aplikasi Google Docs. Besar sampel sebanyak 582 partisipan. Teknik sampling yang digunakan adalah simple random sampling. Analisis data menggunakan uji Korelasi Pearson. Hasil penelitian partisipan dari jenjang diploma 44,2%, sarjana 26,1%, perawat profesional 18,6%, magister 8,8%, spesialis 1,4%, dan doktor 1,0%. Ada hubungan yang signifikan (p-value < 0,05) antara penguasaan metode pembelajaran online dan dukungan teknologi informasi dengan kemampuan kognitif dan psikomotorik dalam arah yang positif, dan tidak ada hubungan dengan kemampuan afektif. Penguasaan metode pembelajaran dan dukungan teknologi informasi berhubungan dengan pencapaian kemampuan kognitif dan psikomotorik. Metode pembelajaran online khusus diperlukan untuk mencapai kemampuan efektif mahasiswa. Kata Kunci: COVID-19, keperawatan, metode pembelajaran, pandemi, teknologi informasi